#TITLE_ALTERNATIVE# - MILADI SYAHDAN (NIM : 13607036); Pembimbing : Dr.Ing. M. Agoes Moelyadi, ST, M.Sc, IRFAN
Flying car is one of a proposed solution to cope with the unbalanced growth of roads to growth of traffic volume. The Zenith flying car in this research is designed based on urban operation needs using sidepod concept as the lift generation device. The design is a composite design using both high performance car and aircraft design with consideration on the designed operation condition and sidewind performance even thought sidewind will not be observed in this particular research. The research is conducted using CFD with 3D complex geometry structured mesh. There are various mesh which is based from 3 main mesh that is mesh for 150%, 25%, and 10% distances cases. Each mesh has consideration for physical condition such as boundary layer, ground, fan inlet flow velocity etc. All of the numerical simulation is conducted on sea level condition and typical European highway vehicle velocity. Analysis is conducted to observed effects of angle of attack to aerodynamicsÃ‚Â’ characteristic without ground effect. Comparison between with and without sidepod configuration to determine the effectiveness of the sidepod. Ground effect is observed from the changes in force and vortex characteristic due to variance of distance to ground.